The Lingering Conflict : Israel, The Arabs, and the Middle East 19482012 - Rabinovich, Itamar, 1942- (Book collections on Project MUSE., 2013)
"A detailed history and analysis of Arab-Israeli relations and the conflict between two peoples claiming the same land, exploring through firsthand experience how these relations have been shaped over the years and assessing the prospects for a peaceful future"--Provided by publisher.